1979
DOI: 10.1111/j.1432-1033.1979.tb13079.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Proinsulin mRNA from Rat B‐Cell Tumor

Abstract: Proinsulin mRNA was purified from rat B-cell tumor induced by streptozotocin and nicotinamide. The purification was achieved through the use of oligo(dT)-cellulose chromatography and sucrose gradient centrifugation. As judged by translational activity in a cell-free protein-synthesizing system of wheat germ, proinsulin mRNA was purified 362-fold from total nucleic acid of the B-cell tumor. Purified proinsulin mRNA migrated as a single symmetrical peak on sucrose gradient centrifugation and as a single band on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Rat I and II preproinsulin mRNA levels have been measured in rat islets [31] and insulinoma ceils [30,32] and shown to be present in approximately equal amounts. It has, furthermore, been shown that both rat preproinsulin mRNAs appear to be regulated coordinately in vivo following fasting and refeeding of rats with sucrose [31].…”
Section: Discussionmentioning
confidence: 99%
“…Rat I and II preproinsulin mRNA levels have been measured in rat islets [31] and insulinoma ceils [30,32] and shown to be present in approximately equal amounts. It has, furthermore, been shown that both rat preproinsulin mRNAs appear to be regulated coordinately in vivo following fasting and refeeding of rats with sucrose [31].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted with phenol/chloroform at pH 9 [5] and purified by LiCl precipitation as previously described [9]. A 10% aliquot of total RNA was stored at -80°C for cDNA hybridisation.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted with phenol-chloroform according to Itoh et al (18). Poly A+ RNA was separated out by chromatography on oligo(dT)-cellulose T7 as described by Aviv and Leder (19).…”
Section: Ilmentioning
confidence: 99%